2014
DOI: 10.1155/2014/628518
|View full text |Cite
|
Sign up to set email alerts
|

Whole Body Vibration Exercises and the Improvement of the Flexibility in Patient with Metabolic Syndrome

Abstract: Vibrations produced in oscillating/vibratory platform generate whole body vibration (WBV) exercises, which are important in sports, as well as in treating diseases, promoting rehabilitation, and improving the quality of life. WBV exercises relevantly increase the muscle strength, muscle power, and the bone mineral density, as well as improving the postural control, the balance, and the gait. An important number of publications are found in the PubMed database with the keyword “flexibility” and eight of the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 86 publications
3
42
0
2
Order By: Relevance
“…The sample size was determined based on a study by Sá-Caputo et al [26], involving individuals with MetS exposed to WBVE, using an online calculator of the Laboratório de Epidemiologia e Estatística (LEE), Faculdade de Medicina, USP, São Paulo, Brazil [40]. For a statistical power of 95%, a sample size of 13 individuals was calculated [26,40]…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was determined based on a study by Sá-Caputo et al [26], involving individuals with MetS exposed to WBVE, using an online calculator of the Laboratório de Epidemiologia e Estatística (LEE), Faculdade de Medicina, USP, São Paulo, Brazil [40]. For a statistical power of 95%, a sample size of 13 individuals was calculated [26,40]…”
Section: Sample Sizementioning
confidence: 99%
“…Authors evaluated the effects of WBVE on MetS individuals, and important responses were observed, such as improvement of quality of life and flexibility [25,26]. Moreover, WBVE is safe and effective to treat muscle complications in populations with different disorders [27][28][29][30][31] as well as healthy individuals [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…이에, 노인을 대상으로 한 장기간의 선행연구에서 다양한 결과들이 보고되었는데, 근육 단면적의 증가 [101][102][103] , 골밀도의 증가 104) , 평형성과 유연성 증가 105) , 그리고 복부지방의 감소 Table 1 shows clinical studies with whole-body vibration for older adults. Overall physical factors including muscle strength and power are increased after whole-body vibration intervention.…”
Section: 또한 노인들을 대상으로 한 많은 선행연구에서 근파워와 근기능의 향상을 통한 일상생활 움직임 향상에 초점을 unclassified
“…Among the different exercise modalities, whole body vibration (WBV) exercise (21) has gained progressive popularity, being safe and well accepted by the patients. WBV exercises are generated by mechanical vibrations produced in oscillating/vibratory platforms (OVP) and can be transmitted to the body of the individual when is in contact with the OVP (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have already demonstrated the effects of WBV exercise with different protocols in improving muscle strength (25,26), bone formation (25,27), balance (28), flexibility (29,30), function ability (26,27), relief of pain (31) and fatigue (32). Moreover, investigations have shown the WBV exercise benefits in the rehabilitation programs of patients with chronic diseases, such as metabolic syndrome (24), chronic obstructive pulmonary disease (33)(34)(35), fibromyalgia syndrome (36), multiple sclerosis (32,37), rheumatoid arthritis (27) and cancer therapy-related morbidities (39).…”
Section: Introductionmentioning
confidence: 99%